Alarming levels of stigma toward generalized dystonia: A cross-cultural comparison. (2020) - Gharzai, Laila; Harney, Jennifer; Higgins, Suzanne; High, Robin; Xu, Liyan; Inciarte, Douglas; Ameer, Muhammad Atif; Torres-Russotto, Diego
Abstract: Introduction: Although stigma has been linked to poor quality of life, studies examining its prevalence in dystonia are lacking. Our objective was to determine prevalence and predictors of stigma against generalized dystonia in diverse cultural settings. Method: Participants were 273 (65.9% female) patients and visitors approached at primary care clinics from three populations: León, Nicaragua (92 participants); a mostly-Hispanic Clinic in Omaha, NE USA (85 participants); and a mostly-non-Hispanic population in Omaha, Nebraska (96 participants). Participants learned about generalized dystonia, epilepsy and schizophrenia through reading a small vignette and viewing videos, followed by a questionnaire designed to identify stigma. We compared levels of stigma between dystonia and other conditions at different sites and measured variables that could affect them. Results: Prevalence of stigma was high toward dystonia (33.00%), similar to epilepsy and lower than schizophrenia. The results showed a complex relationship between the studied variables and level of stigma, especially with age. Female gender predicted more stigmatizing answers. Country of origin, level of education and self-identification of Hispanic ethnicity did not affect stigma. Learning more personal information about the dystonia patient decreased dystonia, a proof that unjustified preliminary negative judgment was present. Conclusions: Stigma against generalized dystonia was very prevalent across all the communities studied. Demographic and socio-cultural variables had different correlations to level of stigma, underlying the complexity of this problem. The alarming levels of stigma against dystonia justify further studies on how to minimize its impact on our patients. Highlights: Prevalence of stigma is high toward generalized dystonia. Female gender predicted more stigmatizing answers. Country of origin and ethnicity did not affect stigma against dystonia. Stigma was similar at all levels of education.